PLAID syndrome: Characteristic presentation and a novel therapeutic option. Issue 1 (21st October 2019) - Shea, James; Huynh, Thy; Milner, Joshua; Chamlin, Sarah
Abstract: PLCG2 ‐associated antibody deficiency and immune dysregulation (PLAID) is an autosomal dominant inherited disease caused by genomic deletion in PLCG2 and is characterized by cold urticaria, humoral immune deficiency, cutaneous granulomas, and autoimmune disease. The patient described in this case had a typical presentation for a PLAID phenocopy and experienced intense pruritus, a common complication of PLAID, starting in early childhood. After trialing H1 and H2 blockers with no improvement, oral glycopyrrolate was used with near resolution of the patient's symptoms. Given that the pruritus in PLAID is related to sweat‐induced evaporative cooling, practitioners who encounter this disease should consider glycopyrrolate in their management of PLAID‐associated pruritus.